Thrombosis and antiphospholipid antibodies in Japanese COVID-19: based on propensity score matching - Oba, Seiya; Hosoya, Tadashi; Kaneshige, Risa; Kawata, Daisuke; Yamaguchi, Taiki; Mitsumura, Takahiro; Shimada, Sho; Shibata, Sho; Tateishi, Tomoya; Koike, Ryuji; Tohda, Shuji; Hirakawa, Akihiro; et al. (Frontiers in Immunology, 2023)
Background： Thrombosis is a unique complication of coronavirus disease 2019 (COVID-19). Although antiphospholipid antibodies (aPL) are detected in COVID-19 patients, their clinical significance remains elusive. We evaluated the prevalence of aPL and serum concentrations of beta-2 glycoprotein I (β2GPI), a major self-antigen for aPL, in Japanese COVID-19 patients with and without thrombosis. Methods： This retrospective single-center nested case-control study included 594 hospitalized patients with COVID-19 between January 2020 and August 2021. Thrombotic complications were collected from medical records. Propensity score-matching method (PSM) (1:2 matching including age, sex, severity on admission, and prior history of thrombosis) was performed to compare the prevalence and titer of aPL (anti-cardiolipin (aCL) IgG/IgM, anti-β2GPI IgG/IgM/IgA, and anti-phosphatidylserine/prothrombin antibody (aPS/PT) IgG/IgM) and serum β2GPI concentration. In addition, PSM (1:1 matching including age and sex) was performed to compare the serum β2GPI concentration between COVID-19 patients and healthy donors. Results： Among the patients, 31 patients with thrombosis and 62 patients without were compared. The prevalence of any aPLs was indifferent regardless of the thrombosis (41.9 % in those with thrombosis vs. 38.7 % in those without, p =0.82). The positive rates of individual aPL were as follows: anti-CL IgG (9.7 % vs. 1.6 %, p =0.11)/IgM (0% vs. 3.2%, p =0.55), anti-β2GP1 IgG (22.6 % vs. 9.7 %, p =0.12)/IgA (9.7% vs. 9.7%, p =1.0)/IgM (0% vs. 0%, p =1.0), and anti-PS/PT IgG (0% vs. 1.6%, p =1.0)/IgM (12.9% vs. 21.0 %, p =0.41), respectively. The aPL titers were also similar regardless of thrombosis. The levels of β2GPI in COVID-19 patients were lower than those in the healthy donors. Conclusion： Although aPLs were frequently detected in Japanese COVID-19 patients, their prevalence and titer were irrelevant to thrombotic complications. While COVID-19 patients have lower levels of serum β2GPI than healthy blood donors, β2GPI levels were indifferent regardless of thrombosis. Although most of the titers were below cut-offs, positive correlations were observed among aPLs, suggesting that the immune reactions against aPL antigens were induced by COVID-19. We should focus on the long-term thromboembolic risk and the development of APS in the aPL-positive patients with high titer or multiple aPLs.